Copper‐Catalyzed Trifluoromethylation–Cyclization of Enynes: Highly Regioselective Construction of Trifluoromethylated Carbocycles and Heterocycles. Issue 43 (23rd September 2013) - Gao, Pin; Yan, Xiao‐Biao; Tao, Tao; Yang, Fan; He, Ting; Song, Xian‐Rong; Liu, Xue‐Yuan; Liang, Yong‐Min
<x xml:space="preserve">Abstract</x> Regioselective trifluoromethylation–cyclization: A method for copper‐catalyzed trifluoromethylation–cyclization of simple enynes using the CC triple bond as a nucleophile is reported for the first time (see scheme). The reaction proceeds efficiently in a highly regioselective manner to give various 5‐ or 6‐exo‐dig carbocycles and heterocycles in moderate to high yields.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>